Antecedents of Adoption of Virtual Reality in Experiencing Destination: A Study on the Indian Consumers. Issue 1 (2nd January 2020) - Vishwakarma, Pankaj; Mukherjee, Srabanti; Datta, Biplab
ABSTRACT: This study has examined the antecedents of adoption of Virtual Reality (VR) among the Indian tourists using the Technology Acceptance Model (TAM). Perceived enjoyment and perceived immersion have been added to the TAM model as two additional antecedents, and their interrelationships and impacts on tourist's intention to adopt VR were examined. Structural equation modelling was used to analyze the responses obtained from 259 respondents. This study has contributed to the literature by establishing interrelationships among the proposed constructs. Further, this study has advanced the TAM in the context of the adoption of VR by Indian tourists while selecting a tourist place.